Persebaran agens hayati Neochetina spp. (Coleoptera: Curculionidae) di jawa barat dan DKI jakarta - Sapdi Sapdi; Damayanti Buchori; Utomo Kartosuwondo; S. Tjitrosemito; Bandung Sahari (Perhimpunan Entomologi Indonesia, 2006)
The establishment of Neochetina spp. as biocontrol agent of waterhyacinth are related to the weevil’s ability to disperse and to increase their population sizes. The objective of this research was to study the distribution and abundance of Neochetina spp. at several areas in West Java and DKI Jakarta. The field research was done in several freshwater ecosystem infested by waterhyacinth, including Cibinong and Lido lakes in Bogor, irigation canal in Karawang, Muara Angke Sanctuary in North Jakarta, and Citarum Hulu river in Purwakarta, during April to August 2004. Coordinate and elevation of the research sites where N. eichhorniae and N. bruchi found were reported, while their abundances were observed by direct hand-collection technique. The results of the research showed that N. eichhorniae was widely distributed and established in most sampling sites, except in Karawang, whereas N. bruchi was not found in any sampling sites. Our observations also indicated that N. eichhorniae was distributed passively so that the weevil couldn’t colonize isolated habitats or locations.